Pembuatan Pupuk Organik Cair Dari Limbah Dapur Bagi Kelompok Tani - khairunnas khairunnas; Asgami Putri; Hamdan Yasid (Asosiasi Dosen Akuntansi Indonesia, 2022)
The increasing volume of waste, especially household waste, and there aren’t any yet of Final Disposal Sites (TPA) and Temporary Disposal Sites (TPS) in Rantau Panjang Village, Rumbai Barat District, Pekanbaru City, requires waste management with simple technology. The application of simple technology is expected to give optimal results in processing and controlling household waste. One method that can be developed is to convert household waste into liquid fertilizer. With the geographical condition of Rantau Panjang Village which is still green, there are several community groups doing simple agriculture. However, with the high price of chemical fertilizers, household spending has increased. For this reason, it is necessary socialization and train to process household waste into Liquid Organic Fertilizer (POC). The training was conducted for several farmer groups in Rantau Panjang Village, Rumbai Barat District. From this socialization, hoped that it will reduce community agricultural spending.